Brand Image Benefit And Satisfaction: Roles of Symbolic, Functional, Social, And Experiential Benefits - Suddin Lada (2018)
The aim of this study is to examine the effects of brand image benefits of symbolic, functional, social, and experiential on the overall satisfaction. A survey using 400 respondents is used to measure these effects. The theoretical and statistical relationship among these constructs are developed and verified by Smart Partial Least square (PLS) statistical software. Result show that symbolic, experiental, and function benefit are significant predictor of overall satisfaction, with experiential benefit as the most important followed by functional benefits. This study provides important implications on marketing and brand positioning.